2019
DOI: 10.1103/physrevb.99.144411
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic theory of spin transport at the interface between a superconductor and a ferromagnetic insulator

Abstract: We theoretically investigate spin transport at the interface between a ferromagnetic insulator (FI) and a superconductor (SC). Considering a simple FI-SC interface model, we derive formulas for the spin current and spin-current noise induced by microwave irradiation (spin pumping) or the temperature gradient (the spin Seebeck effect). We show how the superconducting coherence factor affects the temperature dependence of the spin current. We also calculate the spin-current noise in thermal equilibrium and in no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 62 publications
6
61
0
Order By: Relevance
“…Notably, ⌈Δ V nl th ⌉ Pt,no Al 2 O 3 /⌈Δ V nl th ⌉ Pt,with Al 2 O 3 drops abruptly right below T c (extracted from the Nb resistance R Nb versus T base plot of Figure 2 c), and then it rises progressively as the Nb enters deep into the superconducting state, resulting in a downturn at T base / T c ≈ 0.95 (inset of Figure 2 f). Such a nontrivial behavior is compatible with recent theoretical predictions 29 , 30 and experimental reports 31 , 32 on ferromagnetic insulator (FMI)/SC structures, where (spin-singlet) Cooper pairs from the SC cannot leak into the FMI even if the exchange spin-splitting can still penetrate the SC. 4 So rather well-developed coherence peaks of the QP density-of-states (DOS) at the FMI/SC interface 5 are accessible to the transporting spin current.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Notably, ⌈Δ V nl th ⌉ Pt,no Al 2 O 3 /⌈Δ V nl th ⌉ Pt,with Al 2 O 3 drops abruptly right below T c (extracted from the Nb resistance R Nb versus T base plot of Figure 2 c), and then it rises progressively as the Nb enters deep into the superconducting state, resulting in a downturn at T base / T c ≈ 0.95 (inset of Figure 2 f). Such a nontrivial behavior is compatible with recent theoretical predictions 29 , 30 and experimental reports 31 , 32 on ferromagnetic insulator (FMI)/SC structures, where (spin-singlet) Cooper pairs from the SC cannot leak into the FMI even if the exchange spin-splitting can still penetrate the SC. 4 So rather well-developed coherence peaks of the QP density-of-states (DOS) at the FMI/SC interface 5 are accessible to the transporting spin current.…”
Section: Resultssupporting
confidence: 89%
“…The calculated J s0 qp / J s0 increases largely near T c (0.8 T c – 0.9 T c ), and it decreases exponentially when T < 0.8 T c , reflecting the singularity behavior in a nonequilibrium population of spin-polarized QPs. 29 , 30 , 42 In addition, the peak amplitude of J s0 qp / J s0 is inversely proportional to Δμ m /2Δ 0 SC (inset of Figure 5 a and b), explaining qualitatively the heating power dependence of the transition-state enhancement ( Figure 3 f). Nonetheless, this analysis based on the superconducting coherence factor does not capture the mechanism behind the nontrivial t Nb dependence ( Figure 4 j).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…However, spin splitting of the superconductor enables the precession to pump energy current at linear response, and as its Onsager counterpart, there is nonzero thermal spin torque. This torque arises via the mechanism of [18], in contrast to magnon spin-Seebeck effects [3,16,25] or the in our case small normal-state Mott thermopower [3,29,34], which are not included above.…”
Section: Arxiv:190700424v1 [Cond-matmes-hall] 30 Jun 2019mentioning
confidence: 89%
“…In such systems charge and (non-collinear) spin transport are closely linked and need to be treated on the same footing. Recently there has also been increased interest to couple superconductors to magnets and find out how superconductivity affects the magnetization dynamics, [5][6][7][8][9][10][11][12][13][14][15] including thermally driven effects [16]. On the other hand, recent work has shown that a combination of magnetic and superconducting systems results to giant thermoelectric effects [17][18][19][20] coupling charge and heat currents.…”
mentioning
confidence: 99%